MARKETING ANALYSIS OF GILLNET FISHING YIELD IN PASAR II NATAL VILLAGENATALSUB DISTRICT MANDAILING NATAL REGENCY SUMATERA UTARA PROVINCE - Resmiati Siregar; Hamdi Hamid; Hazmi Arief (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT    This research was carried out in March 2018 In Pasar II Natal VillageNatalSub District Mandailing Natal Regency Sumatera Utara Province. This study aims to find out the marketing channels of fish caught by gillnet drift In Pasar II Natal VillageNatalSub District Mandailing Natal Regency Sumatera Utara Province and to analyze the costs, profits and margins of marketing of fish caught by gillnet drift In Pasar II Natal VillageNatalSub District Mandailing Natal Regency Sumatera Utara Province. The method used in this research is survey method with 35 respondents.            Fish caught by fishermen In Pasar II Natal VillageNatalSub District Mandailing Natal Regency Sumatera Utara Province use gillnet drift consisting of three types of fish, namely Tongkol (Euthynnus affinis), Mackerel fish (Scomberromo commersoni) and Kembung fish (Rastrelliger sp). And fish marketing channels In Pasar II Natal VillageNatalSub District Mandailing Natal Regency Sumatera Utara Province there are two marketing channels, the first is from fishermen to traders to retailers to consumers. Second, from fishermen to retailers to consumers. As for marketing channel I, the highest total marketing costs are found in tuna, which is  IDR 6.000 /kg, total marketing profit of is IDR 12.000/kg, and marketing margin of IDR 14.000/kg. For marketing channel II, the highest marketing costs are in tuna fish, which is IDR 2.400/kg, total marketing profit is IDR 9.200/kg, and marketing margin is IDR  10.000/kg. Keywords: Marketing, Gillnet Drift, Fishermen, Catches, Costs